LEASING SERVICES IN FOREIGN COUNTRIES: EXPERIENCE FOR UKRAINE - CHEBERAKO, Oksana; HNATYUK, Oksana (Scientific journal «World of Finance», 2020)
Introduction. Lack of direct investment has recently forced entrepreneurs to resort the other forms of investment, which makes it relevant to study one of these forms – leasing. The rapid development of leasing activities in foreign countries is due to the fact that it is an advanced method of logistical support of business activity. Due to its advantages, leasing gives wide access to advanced technologies and technologies to business entities. Influencing the macroeconomic dynamics in the country, it activates the process of investment and renewal of fixed assets, creates new jobs, promotes the development of the national economy. The purpose is to study the trends of leasing development in the world and to offer the basic directions of introduction of foreign experience in domestic practice. Methods. The historical, analytical, empirical, inductive-deductive, comparative research methods to implement the principle of objectivity of scientific presentation have been used. Results. The article examines foreign experience and legal support for the development of leasing services. Revealed, globalization, specialization, consolidation, the formation of strategic alliances are the modern tendencies of dynamic development of the world market of leasing services. Conclusions. Suggestions have been made on the need to introduce the foreign experience of leasing development in Ukraine through the improvement of the legislative base, its harmonization with international norms, the creation of infrastructure of the leasing services market, the development of the guarantees system and insurance. Leasing items, that increase banks’ interest through the system of long-term loans, are substantiated.